THE ROLE OF SELF-EFFICACY, ENTREPRENEURIAL KNOWLEDGE, AND BUSINESS MOTIVATION ON BUSINESS SUCCESS OF CULINARY BAREFOOT ENTREPRENEUR IN BANJARBARU CITY - Tuwonaung, Yoren Jhon Elvianus; Anisah, Hastin Umi (Fakultas Ekonomi, Universitas Negeri Jakarta, 2025)
This study aims to determine and analyze: (1) The effect of self-efficacy on business success of culinary barefoot entrepreneur in Banjarbaru City; (2) The effect of entrepreneurial knowledge on business success of culinary barefoot entrepreneur in Banjarbaru City; and (3) The effect of business motivation on business success of culinary barefoot entrepreneur in Banjarbaru City. This study uses quantitative methods with variables of Self-Efficacy, Entrepreneurial Knowledge, Business Motivation, and Business Success. The population of this study were all owners or managers of culinary barefoot entrepreneur in Banjarbaru City. The sampling technique in this study used purposive sampling with a sample size of 80 respondents. The data were processed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS4.0 software. The results of this study prove that: (1) Self-efficacy has a positive and significant effect on business success of culinary barefoot entrepreneur in Banjarbaru City; (2) Entrepreneurial knowledge has a positive and significant effect on business success of culinary barefoot entrepreneur in Banjarbaru City; and (3) Business motivation has a positive and significant effect on business success of culinary barefoot entrepreneur in Banjarbaru City.